Rules of Law and Rights-Terminating Legal Facts in the Mechanism of Legal Regulation - KHOMENKO, Mykhailo M.; KOSTRUBA, Anatoliy V.; KOT, Oleksii O. (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018DO - 10.14505//jarle.v9.8(38).13, 2019)
The article is dedicated to the problem of studying the mechanism of legal regulation of social relations as well as one of its elements, namely, the rule of law. Due to the fact that legal regulation is characterized by general properties, laws and tendencies, the issue of rights-terminating legal facts in the mechanism of legal regulation of civil relations is actual and requires in-depth scientific research. The article aims to determine the place of rules of law and rights-terminating legal facts in the mechanism of legal regulation of social relations. The authors come to the conclusion that the mechanism of achieving the aim of legal regulation should be understood as a consistent chain of changes in individual legal phenomena: legal fact, rights and duties which exist in the civil-legal relations that arose on its basis, implementation of these rights and duties, and if necessary, their protection as well